Uma história da educação domiciliar no Brasil (1996 – 2023) - Botelho, William Marcos (2024)
In the current debates on "Home Education" in Brazil, it is possible to see different political groups disputing the meanings of this term to formalize it as a form of private provision of public education. Various arguments are put forward for this, from "parental power" to freedom of choice in the democratic world. With different social designs, it can be seen that none of these themes are new, although in current documentation "Home Education" is presented as a strand of pedagogical innovation. The aim of this paper is to discuss the historical meanings of "Home Education", emphasizing the political and legal debates presented by the interests of the groups that defend it. It seeks to understand the Home Education agenda, mainly as presented in the legal process proposed by members of civil society. Different groups are in favor of the freedom of Home Education, and are exerting political pressure, but there is a force made up of the relationship between wealthy middle-class families and the speeches of education entrepreneurs, in the sense of the freedom of a curriculum for the "enterprise". The process of composing laws is understood as an experience of composing norms through the symbolic and material disputes that take place in society (THOMPSON, 1998), seeing our relationship with norms as a social dynamic (BOBBIO, 2008). The documents used consist mainly of